Suspicious minds: the psychology of persecutory delusions. - Freeman, D (2007)
At least 10-15% of the general population regularly experience paranoid thoughts and persecutory delusions are a frequent symptom of psychosis. Persecutory ideation is a key topic for study. In this article the empirical literature on psychological processes associated with persecutory thinking in clinical and non-clinical populations is comprehensively reviewed. There is a large direct affective contribution to the experience. In particular, anxiety affects the content, distress and persistence of paranoia. In the majority of cases paranoia does not serve a defensive function, but instead builds on interpersonal concerns conscious to the person. However, affect alone is not sufficient to produce paranoid experiences. There is also evidence that anomalous internal experiences may be important in leading to odd thought content and that a jumping to conclusions reasoning bias is present in individuals with persecutory delusions. Theory of mind functioning has received particular research attention recently but the findings do not support a specific association with paranoia. The threat anticipation cognitive model of persecutory delusions is presented, in which persecutory delusions are hypothesised to arise from an interaction of emotional processes, anomalous experiences and reasoning biases. Ten key future research questions are identified, including the need for researchers to consider factors important to the different dimensions of delusional experience.